The compressive strength of implant-abutment complex with different connection designs - Hsien-Ching Hung; Chiung-Shing Huang; Yu-Hwa Pan (Elsevier, 2019)
Background/purpose: Implant-abutment connection is the component responsible for the transmitting of occlusal force from the crown down to the implant fixture. Different connection geometric structure will lead to different mechanical performance. The purpose of this study was to compare the stability of internal hex Implant -abutment connection with internal hex with Morse taper implant-abutment connection by testing their compressive strength. Materials and methods: This was an in vitro study. The test group and the control group had 8 specimens separately. The test group was internal hex combined with Morse taper implant connection design, and the control group was internal hex connection design. Static force was applied to the specimens at a 30° angle until failure. The testing protocol was designed according to ISO14801 regulations. We compared the compressive strength of both groups. Results: The control group showed significantly higher compressive strength than the test group (p < 0.0001). Conclusions: For the compressive strength of implant abutment complex, incorporating Morse taper design into internal hex connection failed to enhance its mechanical performance. According to this study, internal hex connection has higher compressive strength than internal hex connection combined with Morse taper design. Keywords: Compressive strength, Implant connection, Implant abutment complex, Morse taper, Internal hex